2021
DOI: 10.3390/s21113664
|View full text |Cite
|
Sign up to set email alerts
|

Precise Identification of Prostate Cancer from DWI Using Transfer Learning

Abstract: Background and Objective: The use of computer-aided detection (CAD) systems can help radiologists make objective decisions and reduce the dependence on invasive techniques. In this study, a CAD system that detects and identifies prostate cancer from diffusion-weighted imaging (DWI) is developed. Methods: The proposed system first uses non-negative matrix factorization (NMF) to integrate three different types of features for the accurate segmentation of prostate regions. Then, discriminatory features in the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 48 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…Alyoubi et al [ 28 ] proposed a screening system for DR fundus image classification and lesions Localization to help ophthalmologists determine the patients’ DR stage. Abdelmaksoud et al [ 29 ] developed a CAD system that detects and identifies prostate cancer from diffusion-weighted imaging (DWI). The identification of prostate cancer was achieved using two previously trained CNN models (AlexNet and VGGNet) that were fed with the estimated ADC maps of the segmented prostate regions.…”
Section: Overview Of Contributionmentioning
confidence: 99%
“…Alyoubi et al [ 28 ] proposed a screening system for DR fundus image classification and lesions Localization to help ophthalmologists determine the patients’ DR stage. Abdelmaksoud et al [ 29 ] developed a CAD system that detects and identifies prostate cancer from diffusion-weighted imaging (DWI). The identification of prostate cancer was achieved using two previously trained CNN models (AlexNet and VGGNet) that were fed with the estimated ADC maps of the segmented prostate regions.…”
Section: Overview Of Contributionmentioning
confidence: 99%
“…CNN and TL have been widely used in the prediction of medical conditions using different techniques (CT, MRI, panoramic images)-for example: identification of prostate cancer [19]; prediction of bladder cancer treatment response in CT [20]; detection of maxillary sinusitis on panoramic radiographs [21]; screening for osteoporosis in dental panoramic radiographs (DPR) [22]; cardiac cine segmentation [23] and even COVID-19 detection from chest CTscans [24]. Furthermore, Kats et al have recently shown the potential of applying CNN to detect CAC, using Faster Region-based Convolutional Neural Network (FR-CNN) [25] on a modest set of 65 DPRs reaching a F1 score of 0.77 [26].…”
Section: Introductionmentioning
confidence: 99%
“…CNN and TL have been widely used in the prediction of medical conditions using different techniques (CT, MRI, panoramic images) -for example: identification of prostate cancer [12]; prediction of bladder cancer treatment response in CT [13]; detection of maxillary sinusitis on panoramic radiographs [14]; screening for osteoporosis in dental panoramic radiographs [15]; cardiac cine segmentation [16] and even COVID-19 detection from chest CT-scans [17].…”
Section: Introductionmentioning
confidence: 99%